Removal of acrylic acid (AA) from process water by using alumina - Sabtu, Rahimah (2012)
The presence of acrylic acid (AA) in process water is the major problem in many industries which are using acrylic acid.There is no proper method available to remove acrylic acid from process water and hence the industries incinerating the process water containing acrylic acid to remove it.But,this method consumes large amount of natural gas and in turn leads to high energy consumption and high costing.This research was attempted to remove acrylic acid via batch adsorption process by using alumina.The process water taken from BASF Petronas Chemicals Sdn Bhd containing 4% acrylic acid is used as sample water in this study.The adsorption capacity was tested by varying different temperature,amount of alumina and contact time.The initial and final concentration of acrylic acid was tested using High performance liquid chromatography (HPLC).The performance of adsorption process is modeled using two types of adsorption isotherms namely,Langmuir isotherms and Freundlich isotherm.From the experimental results it was found that the alumina was good in removing AA from process water and Freudlish isotherm describe the process well compared to Langmuir isotherms.